COMICS FOR UNDERGRADUATE SELF-EXPLORATION - Catherine Jenkins (PUPIL: International Journal of Teaching, Education and Learning, 2026)
As well as being artifacts of popular culture, comics are powerful tools for education, persuasion, and exploration of identity. Iconic graphic communication overcomes linguistic and emotional barriers. Using critical examination, Communicating with Comics supports students in using comics to explore personal identity and their place in society. Based on McCloud’s Understanding Comics (1994), theory is augmented by articles on narrative, gender, race, disability, and graphic medicine. Students are exposed to a broad variety of challenging comics including Patti LaBoucane-Benson’s The Outside Circle (2015), Shobo and Shof Coker’s New Masters (2019), and Ellen Forney’s Marbles (2012). As a lower-level liberal, research, writing, and referencing are core course components; however, the capstone assignment is the creation of a 16-24 panel comic book. Student scripts include descriptions of each panel, the action, and speech considering questions like: Is there a conflict and a resolution? Why is this story important to share? What do you want readers to learn or reflect on from this story? Having been exposed to a variety of challenging comics, students see the potential for using comics to tell a range of stories and are given permission to be daring in their comic creation. They rise to the occasion, taking risks by exploring personal territory and exposing their own vulnerabilities. Students have reflected that as well as enjoying the creative aspects of the course, they also find the capstone assignment cathartic. Students are overwhelmed by social media and technology, and this assignment provides an opportunity for them to pause, reflect, and be creative.